Analysis of The Effect of The Application of Financial Accounting Standards (FAS) on The Quality of The Company's Financial Statements - Maryani, Leni; Sopiansah, Veri Aryanto (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of the application of Financial Accounting Standards (FAS) on the quality of financial statements of companies in the West Java region. The problem underlying this research is that there are still financial reports that are less transparent, not in accordance with standards, and not fully reliable by stakeholders. This raises the urgency to evaluate the extent to which the application of FAS contributes to improving the quality of financial information presented by the company. This study uses a quantitative approach with a survey method of 40 companies from various sectors and businethe level of application of FAS can explain 53% of the variation in the quality of financial statementsss scales in West Java Province. The instrument used is a questionnaire, which has been tested for validity and reliability. Data analysis was carried out with simple linear regression to determine the effect between the application of FAS on the quality of financial statements. The results showed that the application of FAS had a positive and significant effect on the quality of financial statements, with a regression coefficient of 0.529 and a significance value (p) of 0.000. The R² value of 0.530 indicates that 53% of the variation in the quality of financial statements can be explained by the level of application of FAS. These results are in line with previous literature that emphasizes the importance of accounting standards in ensuring comparability, relevance, reliability, and understandability of financial statements. Theoretically, this study contributes to the literature by strengthening the empirical linkage between accounting standard compliance and financial reporting transparency, particularly within the context of emerging regional economies such as West Java.